1999
DOI: 10.3354/meps191217
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of suspension-feeding and growth in the green-lipped mussel Perna canaliculus exposed to natural and experimental variations of seston availability in the Marlborough Sounds, New Zealand

Abstract: Responses In feeding behaviour to wide vanatlons in the amount and composition of natural seston were studled In the green-lipped (GreenshellT\'] mussel Perna canaliculus of standard 58 + 2 mm shell length Nutnent acquisition wds pnmanlv regulated by the rate that mussels cleared water of part~cles (I h ' I , which vaned In hyperbol~c relation with the abundance of chlorophyll-rich organics, lather than with the ren~alning organic 01 inorganic components of ava~lable 5eston Maximal clearance rates of about 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
2
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 37 publications
(60 reference statements)
11
101
2
6
Order By: Relevance
“…It has been suggested that the filter pump is working to capacity in mussels, bryozoans and ascidians, stating that pumping rates are maximal at 'normal' food availabilities, and only decline in response to stress under unnaturally low or unnaturally high food conditions, thus, with no evidence of physiological regulation (Riisgard & Larsen 2000, Riisgard & Goldson 1997, Riisgard 2001). We do not agree that the variations in CR observed in various bivalves (Hawkins et al 1999(Hawkins et al , 2001, and here in Ciona intestinalis, Membranipora membranacea and possibly Ascidiella aspersa, are unnatural. The debate possibly hinges on the definition of 'normal' food availabilities.…”
Section: Bryozoansmentioning
confidence: 46%
“…It has been suggested that the filter pump is working to capacity in mussels, bryozoans and ascidians, stating that pumping rates are maximal at 'normal' food availabilities, and only decline in response to stress under unnaturally low or unnaturally high food conditions, thus, with no evidence of physiological regulation (Riisgard & Larsen 2000, Riisgard & Goldson 1997, Riisgard 2001). We do not agree that the variations in CR observed in various bivalves (Hawkins et al 1999(Hawkins et al , 2001, and here in Ciona intestinalis, Membranipora membranacea and possibly Ascidiella aspersa, are unnatural. The debate possibly hinges on the definition of 'normal' food availabilities.…”
Section: Bryozoansmentioning
confidence: 46%
“…FR has also been reported to decline at high S in other species. Navarro & Widdows (1997), for example, found a decline in FR above 300 mg l -1 for the cockle Cerastoderma edule, and Hawkins et al (1999) observed a decline in FR over 1000 mg l -1 in the mussel Perna canaliculus. We did not see this decline of FR for C. gigas within the range of S tested, which suggests that the S above which FR declines is likely to be above 600 mg l -1 for the population of C. gigas in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum ingestion rate and the initiation of biologically significant food rejection occurs in mussels at relatively high particle concentrations (>10 mg l −1 ; e.g. Hawkins et al 1998Hawkins et al , 1999) compared with levels observed at IMTA sites investigated in Canada, Norway, and the Mediterranean (Lander et al 2004, Sarà et al 2009, Reid et al 2010, MacDonald et al 2011, Handå et al 2012a). The following analysis is therefore meant to be applicable to similar environments.…”
Section: Waste Particle Capture Efficiencymentioning
confidence: 99%